2021
DOI: 10.1111/jop.13134
|View full text |Cite
|
Sign up to set email alerts
|

miRNA for the assessment of lymph node metastasis in patients with oral squamous cell carcinoma: Systematic review and metanalysis

Abstract: Background miRNA is one of the advanced epigenetic molecular markers correlating with lymph node metastasis in patients with Oral squamous cell carcinoma (OSCC). Numerous published papers are showing correlation of miRNA with metastasis. There is a need to analyze and validate such correlation. Method English language literature in major databases from the last 20 years was searched using controlled vocabulary and keywords. Strict inclusion and exclusion criteria were followed for selection of studies. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…miRNAs are epigenetic molecular markers associated with lymph node metastasis in OSCC patients. 26 Expectedly, knockdown of miR-518a-3p partially reversed the effects of HOXA11-AS silencing on F I G U R E 4 HOXA11-AS silencing inhibited EMT in CSCs. HOXA11-AS was knocked down or overexpressed in CD133 + SCC15 and CD133 + SCC9 cells, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…miRNAs are epigenetic molecular markers associated with lymph node metastasis in OSCC patients. 26 Expectedly, knockdown of miR-518a-3p partially reversed the effects of HOXA11-AS silencing on F I G U R E 4 HOXA11-AS silencing inhibited EMT in CSCs. HOXA11-AS was knocked down or overexpressed in CD133 + SCC15 and CD133 + SCC9 cells, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…miRNAs are epigenetic molecular markers associated with lymph node metastasis in OSCC patients 26 . Expectedly, knockdown of miR‐518a‐3p partially reversed the effects of HOXA11‐AS silencing on repressing CSC stemness and enhancing cell radiosensitivity, indicating that HOXA11‐AS modulated the stem cell stemness and radiosensitivity of OSCC by targeting miR‐518a‐3p.…”
Section: Discussionmentioning
confidence: 96%
“…The study of miRNA holds promise. Different systematic reviews have also concluded that they are potential biomarkers for OSCC and OPMDs [ 11 , 72 , 73 ]. The main issue is, as with many of the other markers, is that apart from mir-21, which was assessed by two studies [ 47 , 48 ], the salivary expression of all other miRNAs, has been analyzed by single studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, miRNAs have taken a prominent role in the study of non-coding RNAs [ 281 ]. Many studies have focused on the role of miRNAs in the pathophysiology of various diseases such as cancer, and neurodegenerative and immune-mediated diseases [ 282 , 283 , 284 , 285 , 286 ]. As knowledge has advanced, it has become apparent that the most important targets of miRNAs are the genes that regulate the complicated inflammatory process [ 287 , 288 , 289 ].…”
Section: Discussionmentioning
confidence: 99%